Prospects and Problems of Medical Tourism in China - Yuaner, MA; Jabar, Juhaini Binti (International Journal of Psychosocial Rehabilitation, 2020)
China has a long history and culture of traditional medicine, along with the increasingly sophisticated Western medical technology, is still seriously underdeveloped in the global healthcare travel industry. A massive population, lastingly uneven distribution of medical resources in the country, and the advancement of medical technology and the affordability of medical procedures in foreign countries, prompt China to become a major medical tourists-generating country for the global business (Pualo., 2018). The global medical tourism market was valued at 53,768 million in 2017 (“The global medical tourism market,” 2019), but China accounted for less than 100 million, lagging far behind other Asian countries including Thailand, India and Malaysia.